Świat Dysku w przekładzie - Janusz, Alicja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The Discworld by Terry Pratchett is one of the most famous English fantasy series in the world. It has been translated into several languages, including Polish. The text, however, caused several translation difficulties and problems which have been solved in different ways by Piotr Cholewa, the author of the translation. These problems and solutions are the subject of this article that presents samples of translation with a short commentary.